Community service and cess: towards students' personal development - Alias, Asmidar; Mohamad Bhkari, Norshariza; Zainuddin, Mohd Razmi; Yaccob, Ahmad Amzari (Universiti Teknologi MARA, 2009)
Community service is a volunteer act which is performed for the benefits of the public or its institutions. The benefits vary from the psychological to social and cognitive benefits. The paradigm shift in education, which requires students to develop moral and ethical skills, needs more than classroom activities. The Civil Engineering Student Society in Universiti Teknologi MARA Pahang, known as CESS, provides a platform for students to develop their skills in many ways. One of the consistent activities performed by CESS to achieve this objective is through its community service programmes. A discussion on community service and the dual role played by CESS in developing students' skills, as well as outreaching the community, is put forward in this paper.